Association Analysis of Polymorphisms with Aspirin-Exacerbated Respiratory Disease in a Korean Population - Jin Sol Lee; Joon Seol Bae; Byung-Lae Park; Hyun Sub Cheong; Jeong-Hyun Kim; Jason Yongha Kim; Suhg Namgoong; Ji-On Kim; Choon-Sik Park; Hyoung Doo Shin (Genomics & Informatics)
The tyrosine-protein kinase Tec (TEC) is a member of non-receptor tyrosine kinases and has critical roles in cell signaling transmission, calcium mobilization, gene expression, and transformation. TEC is also involved in various immune responses, such as mast cell activation. Therefore, we hypothesized that TEC polymorphisms might be involved in aspirin-exacerbated respiratory disease (AERD) pathogenesis. We genotyped 38 TEC single nucleotide polymorphisms in a total of 592 subjects, which comprised 163 AERD cases and 429 aspirin-tolerant asthma controls. Logistic regression analysis was performed to examine the associations between TEC polymorphisms and the risk of AERD in a Korean population. The results revealed that TEC polymorphisms and major haplotypes were not associated with the risk of AERD. In another regression analysis for the fall rate of forced expiratory volume in 1 second (FEV1) by aspirin provocation, two variations (rs7664091 and rs12500534) and one haplotype (TEC_BL2_ht4) showed nominal associations with FEV1 decline (p = 0.03-0.04). However, the association signals were not retained after performing corrections for multiple testing. Despite TEC playing an important role in immune responses, the results from the present study suggest that TEC polymorphisms do not affect AERD susceptibility. Findings from the present study might contribute to the genetic etiology of AERD pathogenesis.